Necesidad de reforma del artículo 63 del reglamento de la policía judicial a fin reducir los índices delictivos y casos de impunidad por la falta de agentes especializados en criminalística, en la ciudad de Machala en el año 2010. - Anguizaca Romero, Karen Tatiana (2011)
In punishment, which accounts for 11% of the crimes committed, we also appreciate several robberies by means of scopolamine, robberies in banking agencies, assaults to gas stations, adjustments of accounts to this cases and that does not exist by the delicacies This situation record is necessary that every day the media outline these.